Mass warfare and the welfare: State causal mechanisms and effects - Herbert Obinger; Klaus Petersen (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2014)
The question whether and how warfare has influenced the development of advanced Western welfare states is contested. So far, scholarly work either focused on the trade-off between military and social spending or on case studies of individual countries. What is missing, however, is a systematic comparative approach that is informed by an explicit consideration of the underlying causal mechanisms. This paper outlines an agenda for a comparative analysis of the warfare-welfare state nexus. By distinguishing between three different phases (war preparation, warfare, and post-war period) it provides a comprehensive analysis of possible causal mechanisms linking war and the welfare state and provides preliminary empirical evidence for war waging, occupied and neutral countries in the age of mass warfare stretching from ca. the 1860s to the 1960s. – – Die Frage, ob und wie Kriege die Entwicklung von westlichen Wohlfahrtsstaaten beeinflusst haben, ist in der Literatur umstritten. Bislang fokussierte die Forschung entweder auf den Zielkonflikt zwischen Sozial- und Militärausgaben oder untersuchte einzelne Länder. Demgegenüber fehlt bislang ein systematischer Vergleich, der auch die relevanten Kausalmechanismen in den Blick nimmt. Dieses Arbeitspapier skizziert eine Forschungsagenda für eine vergleichende Analyse der Wechselbeziehung zwischen Krieg und Sozialstaat. Unter Berücksichtigung von drei Phasen (Kriegsvorbereitung, Konfliktphase und Nachkriegszeit) werden mögliche Kausalmechanismen vorgestellt, wie militärische Konflikte den Sozialstaat im Zeitalter des Massenkriegs (ca. 1860 - 1960) beeinflusst haben. Schließlich werden erste empirische Befunde für kriegsführende, neutrale und okkupierte Länder präsentiert.
Keywords: 300